Rethinking the neonatal transport ground ambulance - Carlo Bellini; Martina de Biasi; Maurizio Gente; Luca A. Ramenghi; Roberto Aufieri; Diego Minghetti; Silvia Pericu; Martina Cavalieri; Niccolò Casiddu; on behalf of the Neonatal Transport Study Group of the Italian Society of Neonatology (Società Italiana di Neonatologia, SIN) (BMC, 2019)
Abstract Objectives This article describes the detailed project aimed to realize a dedicated ground ambulance for neonatal emergency transport service (NETS). To date, the European Community rules specify requirements for the design, testing, performance, and equipping of road ambulance used for transport and care of adult injured or ill patients, completely ignoring neonatal transport. Methods The project consisted of electric and gas supply planning, interior design taking into account ergonomic and occupant protection principles, both during travel and during medical care performances. Results A detailed project is presented. Main differences between European Type C ambulance and the new proposed Type D neonatal ground ambulance are the presence on board of air compressed cylinder, iNO cylinders and delivery system, phototheraphy, shock adsorbing stretcher support, cooling device, patient's placenta (refrigeration box), and transcutaneous gas analyzer. Conclusion The European Community rules specify requirements for road ambulance used for transport and care of adult injured or ill patients, completely ignoring neonatal transport. This study describes the detailed project aimed to realize a dedicated ground ambulance for neonatal emergency transport service. This study demonstrated that it is not possible simply to adapt the currently dedicated ambulance for mobile intensive care and resuscitation services (actual type C European Community) in a modern dedicated NETS ambulance; it is of paramount importance suggesting to European Community to introduce a further ambulance type, to be identified type D, strictly reserved to neonatal transport activities.